Pigou's Wealth and Welfare - Young, Allyn A.; Pigou, A. C. (Quarterly Journal of Economics, 1913)
Journal Article Pigou's Wealth and Welfare Get access Allyn A. Young Allyn A. Young Cornell University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 27, Issue 4, August 1913, Pages 672–686, https://doi.org/10.2307/1883448 Published: 01 August 1913